Toni Morrison’s Paradise: A Novel Transforming the Public’s Image of Colored Women - Surányi, Ágnes (FOCUS: Papers in English Literary and Cultural Studies, 2024)
When Toni Morrison’s Paradise was published in 1998, the expectations of both the public and academe were great. Yet critical responses show disappointment or embarrassment at best, misunderstanding at worst. I have found that most reviews are in complete disagreement on relevant points.